Occhio alla salute — le riflessioni linguistiche sul concetto di salute nella lingua italiana - Brandt, Anna (Neophilologica, 2013)
The article aims to analyse — on the basis of cognitive linguistics — the concept of health in Italian and some of its relations to many domains of people’s life. Various idiomatic expressions are examined with the focus on determining the way of perceiving a given notion and its conceptual content. The analyses which were conducted within the framework of master’s thesis of the author led to conclusion that health, which is an abstract notion, is often expressed by the metaphors which reveal a great part of perception, values and attitudes. Italians most often associate health with a person, thus the examined notion is equipped with the qualities and attributes characteristic for humankind.